Surviving the Oregon Trail, 1852 - Rau, Weldon W. (Washington State University Press, 2001)
The 1852 overland migration was the largest on record, with numbers swelled by Oregon-bound settlers as well as hordes of gold-seekers destined for California. It also was a year in which cholera took a terrible toll in lives. Included here are firsthand accounts of this fateful year, including the words and thoughts of a young married couple, Mary Ann and Willis Boatman.
Keywords: Boatman, Mary Ann -- Diaries.; Boatman, Willis -- Diaries.; Boatman, Mary Ann.; Boatman, Willis.; Oregon National Historic Trail -- History.; Overland journeys to the Pacific.; Frontier and pioneer life -- West (U.S.); West (U.S.) -- Description and travel.; West (U.S.) -- History -- 1848-1860.; Pioneers -- West (U.S.) -- Biography.; West (U.S.) -- Biography.; Voyages par terre jusqu'au Pacifique.; États-Unis (Ouest) -- Histoire -- 1848-1860.; États-Unis (Ouest) -- Descriptions et voyages.; Oregon National Historic Trail -- Histoire.; Frontier and pioneer life.; Pioneers.; Travel.; United States -- Oregon National Historic Trail.; West United States.; 1848-1860; Biographies.; Diaries.; History.